2021
DOI: 10.3389/fnhum.2021.653069
|View full text |Cite
|
Sign up to set email alerts
|

Training-of-Trainers Neuroscience and Mental Health Teacher Education in Liberia Improves Self-Reported Support for Students

Abstract: Education programs have been central to reestablishing social norms, rebuilding public educational institutions, and addressing public attitudes toward mental illness in Liberia following a protracted civil war and the Ebola epidemic. The aim of this study was to determine if a program combining an understanding of neuroscience with mental health literacy content could increase teachers’ awareness of students’ mental health issues and produce changes in teacher attitudes and classroom practices. A tiered Train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
0
19
0
1
Order By: Relevance
“…Neuroscience PD has also been successfully implemented in a tiered manner, with initial participants (Tier I) running workshops for additional teachers (Tier II) (Brick et al, 2021a(Brick et al, , 2021b. Teachers in both tiers reported increased self-efficacy, motivation, and self-responsibility, measures considered as important components of teacher competency (Brick et al, 2021a).…”
Section: How Teachers Apply Neuroscience Knowledge Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroscience PD has also been successfully implemented in a tiered manner, with initial participants (Tier I) running workshops for additional teachers (Tier II) (Brick et al, 2021a(Brick et al, , 2021b. Teachers in both tiers reported increased self-efficacy, motivation, and self-responsibility, measures considered as important components of teacher competency (Brick et al, 2021a).…”
Section: How Teachers Apply Neuroscience Knowledge Of Studentsmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that neuroscience knowledge is useful for teachers, justifying its application in education (Dubinsky et al, 2013; Owens & Tanner, 2017). Teachers utilized neuroscience as a framework to guide both planned and in‐the‐moment pedagogical decisions and as a lens on student capabilities (Brick et al, 2021b; Chang, Schwartz, Hinesley, & Dubinsky, 2021; Friedman, Grobgeld, & Teichman‐Weinberg, 2019; Tan & Amiel, 2019). PD experiences around neuroscience also improve teacher competencies of self‐efficacy, motivation, self‐regulation, and self‐responsibility for student outcomes (Brick et al, 2021b), as well as positively impacting teachers' student‐centered pedagogical practices (MacNabb et al, 2006; Roehrig, Michlin, Schmitt, MacNabb, & Dubinsky, 2012; Schwartz, Hinesley, Chang, & Dubinsky, 2019).…”
Section: Figmentioning
confidence: 99%
“…Между тем работы зарубежных коллег показывают, что после магистерского курса, посвященного нейробиологии обучения и памяти, преподаватели, не имеющие отношения к естественным наукам, изменяют методические подходы к обучению, используя идеи нейробиологии . Понимая как стресс и психологическое травмирование могут негативно сказываться на обучении, педагоги в меньшей степени используют подавляющие и авторитарные способы влияния и оказывают большую социальную и эмоциональную поддержку обучающимся (Brick et al, 2021).…”
Section: концептуальные и прикладные перспективы использования достижений нейронаук в профессиональном образованииunclassified
“…Alternatively, research demonstrates that neuroscience concepts can be used to directly improve teachers’ understanding of student learning and teachers’ need to increase metacognition ( Blackwell et al, 2007 ). Recent evidence suggests that professional developments that focus on neuroscience have the capacity to build education self-efficacy, motivation, and personal responsibility ( Brick et al, 2021b ). Chang and colleagues demonstrated that teachers who participated in a graduate-level professional development course that explored educational neuroscience concepts, shifted their focus from content and classroom management issues to their students’ needs, recognizing the importance of their students’ experiences and desire to be agents of their own learning ( Chang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%